Pleural Effusion: An Uncommon Manifestation of Hepatitis - Shahi, Rejina; Bhatta, Narendra; Mishra, Deebya Raj; Acharya, Achyut Bhakta; Verma, Avatar (Journal of Nepal Health Research Council, 2022)
Hepatitis A virus infection is the commonest form of hepatitis in pediatric age group and common health problem in developing countries due to poor sanitation. The clinical spectrum of hepatitis A virus infection ranges from asymptomatic infection to fulminant hepatitis and the symptoms are primarily hepatobiliary or constitutional. Here, we present a case of 16 years old male who presented with complains of fever, vomiting, anorexia, right sided abdominal pain, shortness of breath and cough. On clinical examination, patient has hepatomegaly and decreased breath sounds on right sided mammary, infra- mammary and infra scapular region. Blood investigations showed aminotransferases while pleural effusion and ascites with thickened gall bladder were found in chest x-ray and abdominal ultrasonography respectively. In absence of others causes, pleural effusion can be a rare complication of hepatitis A. Thus, this complication should be kept in mind in endemic countries in clinically matching scenarios. Keywords: Acalculous cholecystitis; ascites; hepatitis A; pleural effusion